Pengaruh Profesionalisme dan Motivasi Kerja terhadap Kinerja Karyawan RSI Ibnu Sina Payakumbuh - Delita, Selwi; Bila, Aziza; Ningsih, Yulia (Journal of Education on Social Science (JESS), 2024)
Public service is very important in Indonesia. The hospital is one of the public services engaged in the health sector. In providing health services to the community, the Ibnu Sina Payakumbuh Islamic Hospital requires good performance. Good performance in an organization will be obtained if it is supported by professionalism and high work motivation from its employees. The purpose of this study was to determine the effect of professionalism on employee performance, the effect of work motivation on employee performance, and the effect of professionalism & work motivation on employee performance at Ibnu Sina Payakumbuh Islamic Hospital. In this study using quantitative methods. The population in this study were all employees of RSI Ibnu Sina Payakumbuh, totaling 213 people. The sample in this study was taken using a total sampling technique, namely the entire population. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique uses multiple linear regression tests through the t test and f test. The results of the study show that there is a direct and significant influence between the variables of professionalism and work motivation on performance either partially or simultaneously.